Analisis Pengaruh Pengalaman Keuangan Dan Tingkat Pendapatan Terhadap Perilaku Keuangan Keluarga Di Kecamatan Purwokerto Timur - Wida Purwidianti; Rina Mudjiyanti (Benefit: Jurnal Manajemen dan Bisnis, 2016)
This study entitled "Effect Analysis of Financial Experience and Income Level Toward Family Financial Behavior In District East Purwokerto. This study took a sample of 85 heads of families living in six villages in the district of East Purwokerto. The results showed financial experience have a significant positive effect on the behavior of the family finances. While the variable income levels have no significant impact on the financial behavior of families in East Purwokerto.